2014
DOI: 10.1177/0898264314551332
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Health and Disability Among Older Adults in Same-Sex Cohabiting Relationships

Abstract: Objectives The present study compared indicators of impaired health and disability between older adults in same-sex cohabiting relationships and their peers in opposite-sex cohabiting relationships. Methods Data were obtained on men (n=698) and women (n=630) aged 50 years and older and in self-reported same-sex relationships from the National Health Interview Survey. Multiple regression analyses were conducted to estimate differences in physical health, mental health and disability status. Results Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 36 publications
6
33
0
3
Order By: Relevance
“…Social relationships and social networks were assessed for their presence, size, and impact. One study found that same-sex relationships may be uniquely protective, as same-sex couples reported fewer chronic conditions and were less likely to report poor health than heterosexual couples [21]. Being partnered, having greater social support, and having larger social networks were associated with positive quality of life [59, 81], lower rates of disability, and fewer symptoms of depression [63].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social relationships and social networks were assessed for their presence, size, and impact. One study found that same-sex relationships may be uniquely protective, as same-sex couples reported fewer chronic conditions and were less likely to report poor health than heterosexual couples [21]. Being partnered, having greater social support, and having larger social networks were associated with positive quality of life [59, 81], lower rates of disability, and fewer symptoms of depression [63].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies also used participant observation in addition to interviews [16-18]. A majority of the studies relied on community-based samples (85.1%), with 4.5% utilizing population-based representative data ( n = 3) [19-21]. Most of the studies incorporated multiple types of recruitment, most commonly outreach via health, social, and other community-based service organizations or businesses (54.8%), snowball sampling (27.4%), internet/social media (23.3%), and flyers and publications such as newsletters and newspapers (20.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Informal supports (i.e., caregiving) have significant importance for older LGBT adults since many have no children or, in some cases, limited family (due to estrangement) to rely on for help. However, older LGBT adults tend to avoid formal supports (e.g., nursing homes) since they are reputed for being discriminatory or misunderstand this group's needs (Gonzales & Henning-Smith, 2014). Thirty-four percent of LGBT caregivers provide care to a partner/spouse compared to 32% in the heterosexual community (American Society on Aging & MetLife, 2010).…”
Section: General Caregiving Challengesmentioning
confidence: 97%
“…LGBT caregiving As evidenced by the AIDS pandemic, the LGBT community has demonstrated great resiliency and a heightened capacity to care for each other (Gonzales & Henning-Smith, 2014). Informal supports (i.e., caregiving) have significant importance for older LGBT adults since many have no children or, in some cases, limited family (due to estrangement) to rely on for help.…”
Section: General Caregiving Challengesmentioning
confidence: 99%
“…Quando comparados aos heterossexuais, é mais frequente encontrar LGB sem filhos e gays e bissexuais masculinos vivendo sozinhos. 5,23,24 Contrastando com esses dados, um estudo brasileiro comparou 40 heterossexuais e 40 homossexuais, com média de idade de 58 anos, e não encontrou diferença em relação ao contato familiar entre os dois grupos, rejeitando o estereótipo de que homossexuais mais velhos seriam solitários e socialmente isolados. Nesse estudo, identificar-se como homossexual era um critério necessário à participação.…”
Section: Estudos Com a População Idosaunclassified